Modelling, Impedance Design, and Efficiency Analysis of Battery Assists PV tied Quasi-Z source inverter - T.K.S Sathayanarayanan; M Ramasamy; C Bharatiraja; JL Munda (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The photovoltaic (PV) power cohort becoming more and more attractive in modern power systems era to meet out the power demand in the globe. Consequently, the extraction of maximum power and reduced power electronics stuff for PV based power generation system research studies are growing continuously to meet out the large power-scale/high-voltage grid-tie demands. In this junction, to improve the efficiency of the existing PV tied Quasi-Z source inverter (QZSI), in this paper the new attempt has proposed here by connecting two batteries across to the QZ capacitors. When a battery connected across each capacitor, this system can deliver power to the load power when the PV panel outputs a variable power with fluctuations. The battery can be charged or discharged without any extra circuit, because of the unique impedance network of QZSI. New PWM techniques and principles are proposed to control the new energy stored QZSI when applied to the PV power system. They can control the inverter output power and manage the battery power simultaneously. The operating principle and power flow of this system are analysed. The Simulated and experimental results through using the planned 0.2-kW prototype validate the proposed analytic model and the design method. In addition, this paper analyzes all of the functioning states for a QZSI and calculates the power loss.